The Study of Serum GOT(Glutamic Oxalacetic Transaminase) Activity and Some kinetic Parameters in Patient with Pulmonary Tuberculosis - Ismahil, P. A.; Hassan, L. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the present study, serum GOT(Glutamic Oxalacetic Transaminase) was purified, the purified enzyme showed the maximum activity at 37ºC and pH 7.5. During purification of serum GOT ion exchange chromatography lead to four separate forms (termed I, II, III and IV). GOT II with the highest specific activity was pure after chromatography on Sephacryl S300. . S.GOT levels were investigated in serum samples from patient with pulmonary tuberculosis .The S.GOT levels were determined at and 37ć .The study revealed that the serum GOT activity was higher in patient of tuberculous pulmonary than in control subjects.The mean serum GOT activity in the patients group was(90±8 IU/L) as compared to control group (27±0.65IU/L) showing a highly significant (p<0.001)difference .The study was concentrated to comprehensive measurement of the rate reaction kinetics(Km,Vmax,Hill coefficient),the first order forward rate constant k1 and half life t1/2 of the enzyme reaction in both normal and tuberculosis serum to evaluate any change In the number and structure of the active site then the rate of enzyme –substrate binding.